Few Losses to Follow-up in a Sub-Saharan African Cancer Cohort via Active Mobile Health Follow-up: The African Breast Cancer—Disparities in Outcomes Study. Issue 10 (8th May 2020) - Foerster, Milena; Anele, Angelica; Adisa, Charles; Galukande, Moses; Parham, Groesbeck; Zietsman, Annelle; Oyamienlen, Christopher Sule; Iwuoha, Kingsley Chukwunyere; Ezeigbo, Esther; Bakengesa, Evelyn; Kaggwa, Agnes; Naamala, Allen; et al.
Abstract: Accurate survival estimates are needed for guiding cancer control efforts in sub-Saharan Africa, but previous studies have been hampered by unknown biases due to excessive loss to follow-up (LTFU). In the African Breast Cancer—Disparities in Outcomes Study, a prospective breast cancer cohort study, we implemented active mobile health follow-up, telephoning each woman or her next-of-kin (NOK) trimonthly on her mobile phone to update information on her vital status. Dates of every contact with women/NOK were analyzed from diagnosis in 2014–2017 to the earliest of September 1, 2018, death, or 3 years postdiagnosis. The cumulative incidence of being LTFU was calculated considering deaths as competing events. In all, 1, 490 women were followed for a median of 24.2 (interquartile range (IQR), 14.2–34.5) months, corresponding to 8, 529 successful contacts (77% of total contacts) with the women/NOK. Median time between successful contacts was 3.0 (IQR, 3.0–3.7) months. In all, 71 women (5.3%) were LTFU at 3 years: 0.8% in Nigeria, 2.2% in Namibia, and 5.6% in Uganda. Because of temporary discontinuity of active follow-up, 20.3% of women were LTFU after 2 years in Zambia. The median time to study notification of a death was 9.1 (IQR, 3.9–14.0) weeks. Although the present study was not a randomized controlled trial, in this cancer cohort with active mobile health follow-up, LTFU was much lower than in previous studies and enabled estimation of up-to-date and reliable cancer survival.